DNA barcoding of the most common marine ornamental fish species spilled over from a small-sized marine protected area, Bali Barat National Park, Indonesia - Dewa Gede Raka Wiadnya; Nia Kurniawan; Anik Martinah Hariati; Septiana Sri Astuti; Akhsan Fikrillah Paricahya; ‪Muhammad Dailami; Wahyu Endra Kusuma (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wiadnya DGR, Kurniawan N, Hariati AM, Astuti SS, Paricahya AF, Dailami M, Kusuma WE. 2023. DNA barcoding of the most common marine ornamental fish species spilled over from a small-sized marine protected area, Bali Barat National Park, Indonesia. Biodiversitas 243: 47-54. Healthy coral reefs within a protected area may function as a source of recruitment to the surroundings through spill-over and export larvae. This study aims to generate a list of common species of marine ornamental fishes for the aquarium trade in Indonesia, mainly collected adjacent to Bali Barat National Park (BBNP). Lived-fish samples were collected from six fish collectors in two villages surrounding BBNP, Sumber Kima, Bali, and Bangsring, Banyuwangi. All species were checked by three active fishermen in both villages for confirmation of the most common species and not belonging to the target. A total of 82 separate groups out of 145 specimens were identified based on their morphological characters. All samples were then sequenced based on mitochondrial cytochrome oxidase subunit I (COI) gene amplification. The sequence read lengths for all the specimens were between 655 and 658 bp. All the findings from this DNA barcoding approach were in line with morphological species identification. Wrasses (Family: Labridae) were the most dominant (41 species) representing the group, followed by Pomacentridae (24 species), Acanthuridae (14 species), Pomacanthidae (14 species) and Gobiidae (10 species). Among the species, only green sergeant, Amblyglyphidodon batunaorum, belonged to the Vulnerable (VU) category based on IUCN criteria. The rest were either Least Concern (LC), Data Deficient (DD), or Not Evaluated (NE). It implied that no catch species were under fishing pressure except for the green sergeant. Considering a total of 28 target species by local fishermen (recorded in an earlier article), small-scale fishermen can easily catch more than 100 species in one trip. The results significantly contributed to the need to generate a list of common ornamental fish species specifically exported from Indonesia as an aquarium trade commodity.